The need for Open Labs for fostering interdisciplinarities in Modern Chemistry. Biocatalysis: a necessary tool for synthetic chemists - Martin, Juliette (Comptes Rendus. Chimie)
Among the different fields of chemical approaches available to the synthetic chemists, biocatalysis is only being slowly adopted, especially due to a lack of know-how and practical experience. However, enzymatic catalysis is a mature technology, and this should encourage more chemists to take further ownership and expand applications in modern chemistry.In the industrial sector, some pharmaceutical companies have been pioneers in the use and acceptance of biocatalysis for the unique properties that enzymes can deliver. In this article, the key concepts for biocatalysis applications will be addressed including some recommendations to new practitioners. Some industrial examples will be presented, such as polycyclization, regioselective acylation, alkene asymmetric bioreduction, meso desymmetrization, kinetic resolution and aldolization. Biocatalysis provides economic and environmental benefits, its awareness should be enhanced, especially in a momentum of conducting hybrid approaches and multicatalysis. Open your Labs!